2020
DOI: 10.3389/fspor.2020.588204
|View full text |Cite
|
Sign up to set email alerts
|

Do Former Elite Athletes Live Longer? New Evidence From German Olympic Athletes and a First Model Description

Abstract: The positive effects of physical activity and recreational sports on health have been well-examined and are well-proven. In contrast, the consequences of extensive elite sports on life expectancy and mortality rates have been described in significantly less unique and comprehensive terms. There is a lack of models that systematically summarize the factors influencing the life span of elite athletes. Therefore, this study identifies the difference between all 6,066 German participants in Olympic Games between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Indeed, it is one of the biases which may be hindering the true impact of certain sports risks that negatively affect highlevel athletes' longevity advantage. Female athletes represent no more than 30% of the Olympic athlete cohorts from other longevity studies around the world and are responsible for an even smaller proportion of deaths, or not included in the cohort at all [13,23,[27][28][29][30][31][32].…”
Section: Mental Illnessmentioning
confidence: 99%
“…Indeed, it is one of the biases which may be hindering the true impact of certain sports risks that negatively affect highlevel athletes' longevity advantage. Female athletes represent no more than 30% of the Olympic athlete cohorts from other longevity studies around the world and are responsible for an even smaller proportion of deaths, or not included in the cohort at all [13,23,[27][28][29][30][31][32].…”
Section: Mental Illnessmentioning
confidence: 99%
“…In particular, "strenuous" joggers (>4 h/wk at >7 miles/h) displayed a trend toward substantially enhanced risk of all-cause mortality (HR, 9.08; 95% CI: 1.87-44.01) compared with "light" joggers. Notably, data on professional athletes are also contradictory, in that some studies reported a higher risk of premature death, 16,17 while others did not. 18,19 Indeed, other studies suggest a "sweet spot" for PA and subsequent clinical outcomes, with either loss of benefit or worse outcomes at very high doses.…”
mentioning
confidence: 99%